Molecular identification of the bacterium acute conjunctivitis by the method of sequensing gen 16S rRNA - Ni'matul Murtafi'ah; Ally Kafesa; Aziz Ansori Wahid (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2024)
Conjunctivitis is the most common eye disease, characterized by contextual inflammation, which can be caused by bacteria. The diagnosis of conjunctivitis is established based various factors, including the patients’s medical history, onset of eye symptoms, non-ocular symptoms, previous disease history, family medical history, allergies, and physical examination of the eyes, which may include assessments of visual acuity and vision field. Some cases of conjunctivitis require laboratory examinations to confirm the diagnosis. These may include cytological examination with Giemsa staining, Chlamydia Diagnostic Test, Nucleic acid amplification tests (NAATs) or Polymerase chain reaction (PCR), and microbiological tests. Microbiological examination helps identify the bacteria responsible for conjunctivitis and aids in treatment by prescribing antibiotics to suppress the growth of the infecting bacteria. While identification tests are not routinely performed, researchers often seek to determine the specific type of bacteria causing conjunctivitis infections, which may require several laboratory tests. Bacterial virulence plays a significant role, with genetic mutations potentially leading to severe infections of varying severity. Virulence genes encode proteins that express pathogenic properties. The species responsible for conjunctivitis can be definitively identified definitively through microbiological examination, utilizing methods such as the 16S Ribosomal RNA Sequencing (rRNA) technique, known for its accuracy and speed. This study aims to analyze the results of rRNA sequencing in cases of acute bacterial conjunctivitis caused by 16S rRNA genotyping. The research employed an exploratory metholodolot, with the results analyzed using the The Basic Local Alignment Search Tool (BLAST) tracking program database on the National Center for Biotechnology Information (NCBI) website. The findings revealed that Sphingomonas paucimobilis encoded the 16S rRNA using Universal Primary 27 F and 1492 R, obtained in a sequence size of 1351bp. The isolate demonstrated similarities to Sphingomonas paucimobilis.